Test Tube Families : Why the Fertility Market Needs Legal Regulation. - Cahn, Naomi R. (NYU Press, 2009)
The birth of the first test tube baby in 1978 focused attention on the sweeping advances in assisted reproductive technology (ART), which is now a multi-billion-dollar business in the United States. Sperm and eggs are bought and sold in a market that has few barriers to its skyrocketing growth. While ART has been an invaluable gift to thousands of people, creating new families, the use of someone else's genetic material raises complex legal and public policy issues that touch on technological anxiety, eugenics, reproductive autonomy, identity, and family structure. How should the use of gameti.